Farm level approach to manage grass yield variation under climate change in Finland and north-western Russia. (December 2015) - Kässi, Pellervo; Känkänen, Hannu; Niskanen, Olli; Lehtonen, Heikki; Höglind, Mats
Abstract : Cattle feeding in Northern Europe is based on grass silage, but grass growth is highly dependent on weather conditions. If ensuring sufficient silage availability in every situation is prioritised, the lowest expected yield level determines the cultivated area in farmers' decision-making. One way to manage the variation in grass yield is to increase grass production and silage storage capacity so that they exceed the annual consumption at the farm. The cost of risk management in the current and the projected future climate was calculated taking into account grassland yield and yield variability for three study areas under current and mid-21st century climate conditions. The dataset on simulated future grass yields used as input for the risk management calculations were taken from a previously published simulation study. Strategies investigated included using up to 60% more silage grass area than needed in a year with average grass yields, and storing silage for up to 6 months more than consumed in a year (buffer storage). According to the results, utilising an excess silage grass area of 20% and a silage buffer storage capacity of 6 months were the most economic ways of managing drought risk in both the baseline climate and the projected climate of 2046–2065. It was found that the silage yield risk due to drought is likely to decrease in all studied locations, but the drought risk and costs implied still remain significant. Highlights: The cost of risk of silage deficit will decrease from the initially high levels. Slightly increasing mean and stable variance of yields decreases the cost of risk. Extra grassland and buffer storage are effective means of risk management. The cost of risk management of silage deficit will still remain significant.